Resposta Elétrica de Um Sensor Infravermelho ao Fluxo de Fertilizantes Agrícolas - Rosa Junior, Álvaro Leonel Rodrigues da (2019)
The advancement of agricultural mechanization and the use of new technologies allow the farmer to increase the productivity of the agricultural areas, that is, to produce in greater quantities, with superior quality, in the same areas. Part of this progress is due to the use of agricultural fertilizers in a coherent way. To assist the farmer in obtaining data necessary for the correct application of fertilizers can be cited the GPS and the equipment that provide information in real time to the operator. Sensors are required for the acquisition of real-time data. In this context, this dissertation was based on the creation of an electro-electronic circuit that could quantify the amount of fertilizer used at each moment, that is, the flow through the signal of an optical sensor. For this, the factors: aperture of the bead, color and size of the beads were used and with the aid of statistical tools it was possible to prove that the optical sensor can be used for this purpose, however, not for any situation.